EFEKTIVITAS PEMBERIAN TUNJANGAN KINERJA DALAM PELAKSANAAN TUGAS POLISI LALU LINTAS (POLANTAS) DI KEPOLISIAN SEKTOR PADANG UTARA - Yolla Aliffia; Nora Eka Putri (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2019)
According to Police Chief Regulation No. 13 of 2015 performance allowance is allowance given as a tribute to the achievements that have been achieved by employees in the National Police in carrying out their duties in order to realize bureaucratic reform. therefore the performance allowance is expected to increase the work productivity of the Indonesian National Police, especially for the Traffic Police. This study aims to determine the effectiveness of the provision of performance allowances in the performance of traffic police duties (POLANTAS) and the factors that influence the implementation of the tasks of the Traffic Police (POLANTAS) in the North Padang Sector Police. This research is a qualitative research with a descriptive approach. in this study the data sources used are primary data and secondary data. data collection by observation, interview, then documentation. Data validity test uses source triangulation techniques. the results of the study indicate that the provision of performance allowances has been effective but has not yet been maximized in the implementation of its duties.